107k views
8 votes
Determine if the expressions are equivalent.

when w = 11:

2w + 3 + 4 4 + 2w + 3

2(11) + 3 + 4 4 + 2(11) + 3

22 + 3 + 4 4 + 22 + 3

25 + 4 26 + 3

29 29

Complete the statements.

Now, check another value for the variable.

When w = 2, the first expression is

.
When w = 2, the second expression is

.
Therefore, the expressions are

.

User SerjG
by
5.2k points

2 Answers

10 votes

Answer:

the first expression is 2 therefore 2 plus the second expression is 4 so 2+4 = 6

User Felix Reckers
by
4.9k points
11 votes

Answer:

the first expression is 2 therefore 2 plus the second expression is 4 so 2+4 = 6

Explanation:

User Denger
by
5.6k points